Readiness of RSUD X in the Implementation of Standard Inpatient Class (KRIS) - Muthiah Amaliah; Zilfadhilah Arranury; Sitti Raodhah (VISIKES, 2026)
The Standard Inpatient Class (Kelas Rawat Inap Standar / KRIS) is a policy embedded within Indonesia's National Health Insurance (Jaminan Kesehatan Nasional / JKN) Programme, designed to achieve equity in inpatient services for all BPJS Kesehatan participants by replacing the three-tier ward system (Classes I–III) with a single minimum standard. This study aimed to analyse the readiness of Daya Regional General Hospital (RSUD Daya), Makassar City, in implementing KRIS. A qualitative case study design was employed. Seven informants were selected through purposive sampling, comprising the Vice Director of Medical Services (key informant), three main informants (Head of Nursing Division, Head of General Affairs, Planning Staff), and three supporting informants (Head of Surgical Ward, Head of Mawar Ward, and a bedside nurse). Data were collected through in-depth interviews, direct physical observation of four representative wards using a 12-criteria KRIS checklist with calibrated instruments (lux metre, thermohygrometer, measuring tape), and hospital document review. Data analysis followed the Miles-Huberman-Saldana model (reduction, presentation, conclusion-drawing), with source and method triangulation applied to verify validity. Results showed that the KRIS policy was well understood at all management levels and phased governance steps had been initiated since 2023. However, implementation remained incomplete due to constrained budget and ageing building conditions. Of 12 technical KRIS criteria, seven were consistently met. Persistent non-conformities were identified in inter-bed spacing, sleep lighting, room humidity, and curtain floor clearance.